APLIKASI TEHNIK EQUALISASI UNTUK MENCEGAH BAROTRAUMA PADA PENYELAM TRADISIONAL - Imroatul Farida; Diyah Arini; Nur Muji Astuti (P3M Universitas Aisyiyah Surakarta, 2020)
The traditional fisherman dive to get a lot of fish, they called traditional divers. The majority of traditional divers do not use equalization techniques while diving, because they have an assume that equalization techniques is not important. The traditional divers also have some signs of barotrauma symptoms such as headaches, ear pain, feeling full in the ears, chest pain, dizziness after diving. The incidence of barotrauma can be reduced if traditional divers can do equalization technique while diving. The target and output are they have better knowledge, skills and awareness to use equalization techniques while diving to prevent barotrauma independently. The method of activities was a seminar and workshop on day 1, demonstration and role play on day 2. The activity was held on 27-28 July 2019, the subject was 70 traditional divers at Kedung Cowek District Surabaya, and was delivered by lecturers and students of STIKES Hang Tuah Surabaya. They have beenbetter improvement in knowledge, skills and awareness of they standard diving procedures, especially in equalization technique to prevent barotrauma.